Aplicação da cromatografia gasosa bidimensional abrangente na caracterização de classes de compostos do petróleo - Silva, Samantha Ribeiro Campos da (2019)
Crude oil is the term used for a wide variety of oils extracted from sedimentary rocks. Due to the variety and complexity of oil matrices an important oil assay is to quantify the content of saturated, aromatic, resin and asphaltene compounds (SARA). However, proper separation of saturated and aromatic components depends on the internal phase of the chromatographic column and on the method used for its quantification. Here works were described: aiming at the relative quantification of nonpolar components present in the saturated petroleum fraction and the use silica gel modified with boric acid to obtain aromatic fractions enriched with nitrogen aromatic compounds. The results showed that GCxGC-qMS technique was efficient in the relative quantification of n-paraffins from C11 to C35 and of branched paraffins in the saturated petroleum fraction. In addition, it allowed the determination of bicyclic, tricyclic, tetracyclic and pentacyclic compounds. In general, the classes of monocyclic and iso-paraffin compounds were the most abundant in the undegraded petroleum saturated fraction. Relative quantification of normal and branched paraffins allowed an understanding of the pour point values of light oils (API gravity greater than 30). The modification of the silica gel (column) with boric acid in the separation of the aromatic components of petroleum was selective to obtain fractions enriched with nitrogen aromatic compounds. However, the nitrogenous components identified in the aromatics fraction are characteristic of resins. Combining the FT-ICR MS (ESI (±) and APPI (±) sources using the Intensity vs DBE graphs) and GCxGC-qMS techniques allowed to ratify the good selectivity of the modified silica gel for the elution of aromatic nitrogen compounds. In the FT-ICR MS analyzes it was possible to visualize intense signals in all ionization sources for the nitrogen classes. The other visualized classes, such as hydrocarbons and oxygenated, were shown as low intensity peaks, corroborating the efficiency of separation of the modified column for nitrogen compounds. The concentration of nitrogenous compounds in crude oils is generally less than 2 wt%, however, they are detrimental to the refining processes and knowledge of the nitrogenous species present in crude oil is desirable. Thus, the methodology using the silica gel modified with boric acid column aimed to supply this important refining demand.